Dispatches from the frontlines of humanity a book of reportage - Videmšek, Boštjan, 1975- (Cambridge Scholars Publishing, 2019)
This book is an in-depth reportage on some of the most defining issues of our time, namely the global refugee crisis, the conflicts displacing these masses of humanity, and the causes behind them. It is also an ode to the vanishing art of the long-form feature or reportage, which is disappearing because many media organisations can no longer afford it, or are unwilling to pay for this kind of time-consuming, on-the-ground journalism.It is essential to keep alive old-school reportage from the field because it provides a human face to the issues challenging our world. It helps pierce the bubble.